Analysis of organochlorine pesticide residues in strawberry by the QuEChERS method with CG Μecd - Zirena Vilca, Franz (2017)
Due their physical end chemical properties, organochlorine pesticides (OCPs) have been occured the contamination the environment and food chain. The consume of this products at low concentration dose represent a potential hazards to human health. The QuEChERS method was adjusted and used for the determination of 12 organochlorine pesticides (α- BHC, β - BHC, heptachlor, dicofol, endosulfan lacton, OP DDD, α - endosulfan, OP DDE, PP DDE, β - endosulfan, PP DDD, endosulfan sulfate) residues in 36 strawberries samples from three markets of the Piracicaba/ Sao Paulo – Brazil, during the period of October 2010 until September 2011. The method involved extraction with ethyl acetate, solid–liquid partition with MgSO4 and CH3COONa followed by dSPE clean up with PSA sorbent. Analyses were carried out with GC–µECD equipment. A HP-5 30 m x 0.32mm x 0.25 µm column was used. The method was validated using a strawberry sample without pesticides residues (blank), spiked at 0.01 and 0.1 mg kg-1; the average recovery by the method varied between 72.9 to 120% with RSD% < 9.6%. The method showed linearity r2 ≥ 0.99 and the LOQ ranged from 0,001 to 0.01 mg kg-1. It could be concluded that QuEChERS method used with GC-µECD is an alternative to determine organochlorine pesticides in strawberries. The results obtained indicate that this method sensitive and has no matrix effect. The method showed six of the samples analyzed have contamination by endosulfan sulfate at the concentrations of 0.003 to 0.02 mg kg-1.